Burrowing Behavior as Robust Parameter for Early Humane Endpoint Determination in Murine Models for Pancreatic Cancer - Brandstetter, Jakob; Hoffmann, Lisa; Koopmann, Ingo; Schreiber, Tim; Schulz, Benjamin; Rosshart, Stephan Patrick; Zechner, Dietmar; Vollmar, Brigitte; Kumstel, Simone (Animals, 2025)
In vivo experiments remain essential for testing new therapeutic approaches against fatal diseases, such as pancreatic cancer. Laws and regulations mandate the continuous improvement of the animal’s welfare during these experiments. One important aspect is the definition of early humane endpoint criteria to prevent the severe suffering of mice through timely euthanasia. In the present study, the welfare of mice in different pancreatic cancer models, and after various treatments for testing their preclinical efficacy, was monitored using body weight change, distress score, perianal temperature, burrowing behavior, nesting activity, and the mouse grimace scale. The ability of each parameter to predict the humane endpoint for each mouse was retrospectively quantified using receiver operating characteristic curve analysis. Burrowing behavior proved to be a robust predictor of the humane endpoint across all different pancreatic cancer models and treatment groups.
CRIS-Team Scopus Importer:2025-05-23
Keywords: animal welfare; early humane endpoint; pancreatic cancer; refinement